Wpływ kryzysu gospodarczego na bezpieczeństwo zdrowia publicznego w UE - Skarżyński, Mirosław (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2013)
The paper emphasizes the significance of health for individual existence and the entire population. It indicates the fundamental elements of health security in the EU. It presents the reasons for and results of economic crisis. The interdependencies between the economic situation and a society’s health are defined. Statistical data provide the basis for the analysis and assessment of the influence the present economic crisis has had on the security of public health in the EU.
The influence of the economic crisis on the security of public health in the EU
Keywords: bezpieczeństwo; zdrowie; gospodarka; kryzys